101k views
3 votes
Please need help on 2 math questions

13. Divide the rational expressions.


(7y-1)/(y2-36)÷(1-7y)/(y+6)


2. Add or subtract as indicated. Write the answer in descending order.

(3n^4 + 1) + (–8n^4 + 3) – (–8n^4 + 2)


A. –13n^4 + 6


B. 3n^4 + 6


C. 3n^4 + 2


D. 19n^4 – 4

1 Answer

5 votes

Question 1:

For this case we have the following expression:


\frac {\frac {y-1} {y ^ 2-36}} {\frac {1-7y} {y + 6}} =\\\frac {(7y-1) (y + 6)} {(y ^ 2-36) (1-7y)} =

We have to:


y ^ 2-36 = (y + 6) (y-6)

Rewriting:


\frac {(7y-1) (y + 6)} {(y + 6) (y-6) (1-7y)} =\\\frac {7y-1} {(y-6) (1-7y)} =

We take common factor "-" in the denominator:


\frac {7y-1} {(y-6) * - (- 1 + 7y)} =\\\frac {7y-1} {- (y-6) * (7y-1)} =\\- \frac {1} {(y-6)}

ANswer:


- \frac {1} {(y-6)}

Question 2:

For this case we must simplify the following expression:


(3n ^ 4 + 1) + (- 8n ^ 4 + 3) - (- 8n ^ 4 + 2) =

We eliminate parentheses keeping in mind that:


+ * - = -\\- * - = +\\3n ^ 4 + 1-8n ^ 4 + 3 + 8n ^ 4-2 =

We add similar terms:


3n ^ 4-8n ^ 4 + 8n ^ 4 + 1 + 3-2 =\\3n ^ 4 + 2

Answer:


3n ^ 4 + 2

User Dynom
by
5.1k points